2014
DOI: 10.1371/journal.pone.0094681
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Epidemiology and Vaccine Effectiveness among Patients with Influenza-Like Illness, Viral Watch Sentinel Sites, South Africa, 2005–2009

Abstract: BackgroundThere is limited data on the epidemiology of influenza and few published estimates of influenza vaccine effectiveness (VE) from Africa. In April 2009, a new influenza virus strain infecting humans was identified and rapidly spread globally. We compared the characteristics of patients ill with influenza A(H1N1)pdm09 virus to those ill with seasonal influenza and estimated influenza vaccine effectiveness during five influenza seasons (2005–2009) in South Africa.MethodsEpidemiological data and throat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The seven studies in healthy adults comprised one randomized controlled trial, and three cohorts and case–control studies each. Seasonal influenza vaccination provided 50–59% protection in healthy adults 18, 44, 45, 46. The 12 studies in children comprised nine randomized controlled trials, one cohort and two case–control studies.…”
Section: Resultsmentioning
confidence: 99%
“…The seven studies in healthy adults comprised one randomized controlled trial, and three cohorts and case–control studies each. Seasonal influenza vaccination provided 50–59% protection in healthy adults 18, 44, 45, 46. The 12 studies in children comprised nine randomized controlled trials, one cohort and two case–control studies.…”
Section: Resultsmentioning
confidence: 99%
“…32 The only other VE study conducted in Africa, a 5-year study in a mostly adult population in temperate South Africa, found that VE ranged from −14.2% to 67.4% annually. 33 In our study, influenza vaccine was moderately effective in preventing laboratory-confirmed influenza illness, despite the generally good match between circulating strains and vaccine strains. Similar findings have been reported previously and may be related to differences in strains that reflect mutations that are not routinely detected.…”
Section: Discussionmentioning
confidence: 54%
“…Due to technical difficulties, the vaccine was only available from late April onwards which may have compounded the low influenza vaccine coverage of 3%, although overall vaccine coverage in previous years in the same population has ranged from 1.8% in 2012 to 5.1% in 2006 2, 3, 4. In the early part of the season, four patients had to be excluded from the analysis due to having received influenza vaccine <14 days prior to onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sites are mainly general practitioners in the private healthcare setting, who submit the majority of specimens during the influenza season. Since 2005, it has also been used to estimate influenza vaccine effectiveness (VE) 1, 2, 3, 4. Recommendations for the use of influenza vaccine are published annually in South Africa 5.…”
Section: Introductionmentioning
confidence: 99%